Autoethnographic Reflections on One’s Own Imperialism - Sofia Gavrilova (The February Journal)
The essay mixes the genre of autoethnographic reflections with an attempt to conceptualize the challenge that members of the Russian academic community in exile are facing on both individual and collective levels. It frames the questions of responsibility, guilt, and identity transformation, and traces the evolution of my personal responses to them as an attempt to document and conceptualize the unavoidable shift in the research field, agenda, positionality, and methods that Russia’s full-scale invasion of Ukraine brought to Slavic/area studies.